Applicant factors contributing to interview selection, ranking determination, and judgement of "Fit" among health service psychology internship training programs. Issue 11 (11th June 2021) - Ingram, Paul B.; Bergquist, Becca K.; Currin, Joseph M.; Schmidt, Adam T.
Abstract: Background: The predoctoral internshipAQ4 training year is the capstone training experience for health service doctoral students. Previous research has explored what applicant characteristics are desired by internship sites and has not thoroughly explored differences between types of sites or criteria importance at different stages of applicant consideration (interview vs. ranking). Aims: We evaluate current perceptions of doctoral student internship applications by training directors. Materials and Methods: Internship training directors of APA‐accredited sites report on the importance of different application materials during interview and ranking decisions. We also compare these rankings across site types. Results: Results indicate that internship sites were generally consistent in their criteria rankings; however, there were also some differences. Intern applicant "fit" continues to be the most important criteria by which applicants are judged at all stages of consideration. Qualitative analysis found that "fit" varied by site across themes of treatment, applicant, and site characteristics. Discussion: We discuss implications in their preparation of internship applications. In addition to the practical guidance for students, we discuss how program changes can increase applicant site competitiveness.